FUNGSI PRODUKSI PADA USAHATANI CABAI DI DESA BATUR, KECAMATAN GETASAN - Zega, Jelita Hati; Prihtanti, Tinjung Mary (Fakultas Pertanian, Universitas Janabadra, 2023)
Farming is one of the activities in the agricultural sector that can benefit the farmer's economy. However, even though chili farming can have a good impact on farmers, not all or many farmers still experience difficulties in managing chili farming in the field of efficient use of production inputs. The research was carried out in Batur Village, Getasan District from April to June 2023. The type of research used in the research was a quantitative descriptive method with Cobb-Douglas production function analysis. In this research, techniques are applied nonprobability namely technique purposive sampling where this technique is the determination of respondents to be used as samples based on certain criteria with a total of 40 farmers as respondents. The research results show that the factors that influence the productivity of curly red chilies are seeds, labor, NPK fertilizer and pesticides. For allocative efficiency, the input of seeds, manure and pesticides is not yet efficient and the input of labor and NPK fertilizer is not efficient. Key words: productivity, curly red chilies, allocative efficiency IntisariUsahatani merupakan salah satu kegiatan dari sektor pertanian yang dapat menguntungkan perekonomian petani. Namun meskipun usahatani cabai dapat memberikan dampak yang baik bagi petani, tidak semua petani dalam mengelola usahatani cabai secara efisien penggunaan input produksi. Penelitian dilaksanakan di Desa Batur, Kecamatan Getasan pada bulan April hingga Juni 2023. Jenis penelitian yang digunakan dalam penelitian yaitu metode deskriptif kuantitatif dengan analisis fungsi produksi Cobb-douglas. Dalam penelitian ini menerapkan teknik nonprobability yakni teknik purposive sampling dimana teknik ini merupakan penentuan responden untuk dijadikan sampel berdasarkan pada kriteria-kriteria tertentu dengan jumlah responden 40 petani. Hasil penelitian menunjukkan bahwa faktor yang mempengaruhi produktivitas cabai merah keriting yaitu bibit, tenaga kerja, pupuk NPK dan pestisida. Kata kunci: produktivitas, cabai merah keriting, efisiensi Alokatif